The critical success factors for implementing data warehouse based excutive information systems - Bestbier, Stuart (My University, 2016)
The use of Information Technology to meet the information needs of senior business executives has been the focus of research effort for many years. Some years ago the emergence of Executive Information Systems (EISs) was seen as the panacea for the information needs of senior executives. More recently, Data Warehouses have been lauded as the ideal technology for providing an integrated view of an organisation's data, while allowing analysis to be performed on this data. Data Warehouses are seen as the ideal vehicle for decision support and the provision of executive information. However, research studies have shown that the failure rate of both EISs and Data Warehouses are very high. This. research identifies, from a theoretical and practical business perspective, those critical factors that contribute to the successful implementation of EISs based on Data Warehouses. This research is aimed primarily at senior business managers and executives, IS/IT managers, and Data Warehouse practitioners, but is also relevant to researchers. The Critical Success Factors (CSFs) can serve as indicators of potential risk, as variables for consideration during planning and management, as a basis for judging the suitability of EISs based on Data Warehouses in particular situations, and as a basis for justifying an invesLnent in Data Warehousing. Chapter one introduces the concepts ofEISs and Data Warehousing. It also discusses the high rate of failure or EIS and Data Warehouse implementations, the need for understanding the CSFs for implementing EI8s based on Data Warehouses, and accounts for the justification of this research. Chapter two critically examines recent literature on EISs and Data Warehouses, and the critical issues surrounding the implementation of EISs based on Data Warehouses. The results of the literature review are presented as a narrative description that is synthesised to develop the theoretical conjecture and associated empirical generalisations for the research. Chapter three develops an argument for the research approach adopted, and presents the research methodology, or procedural framework, within which the research was conducted. Research evidence was gathered by conducting eighteen semi-structured interviews with senior business and 18fT managers, and Data Warehouse practitioners. Chapter four presents the results of the content and interpretive analysis that was conducted on the research evidence. Chapter five reviews the research results against the aim and objectives of the research, and against the theoretical conjecture and empirical generalisations. Based on the results of the review a refined theoretical conjecture is proposed. Chapter six highlights some of the limitations of the research, and provides suggestions for further research
Research dissertation in partial fulfillment of the requirements for the degree of Master of Commerce, submitted to: Faculty of Commerce University of the Witwatersrand Johannesburg South Africa August 1998